Ecotoxicological impacts of cadmium on soil microorganisms and earthworms Eisenia foetida: from gene regulation to physiological processes - You, Rui; Li, Hui; Li, Xia; Luo, Lihui; Wang, Peng; Xia, Han; Zhou, Ya (Frontiers in Environmental Science, 2024)
Cadmium (Cd) is a hazardous heavy metal that is commonly found in the soil and poses significant risks to soil organisms. The toxic effects of Cd on soil microorganisms and earthworms (Eisenia foetida) have been extensively studied, but most studies focused on high Cd pollution levels. Therefore, this study aims to investigate the different responses of soil organisms to moderate and low levels of Cd contamination. According to the study, the presence of 2.5 mg/kg of Cd had a significant impact on the microbial community's composition and diversity. The relative abundance of most microbes decreased, while the abundance of Firmicutes and Actinobacteriota showed a considerable increase. The LEFSE analysis revealed that the Bacillus genus of the Firmicutes phylum can serve as a biomarker in soil contaminated with 2.5 mg/kg of Cd. At the same time, the functional analysis of PICRUSt 2 shows that microorganisms found in polluted soil have a noticeable decrease in their ability to metabolize lipids. On the other hand, our findings indicate that Cd has a detrimental effect on the biomass of earthworms and induces oxidative stress in these animals. The activation of SOD and CAT enzymes in earthworms was carried out to mitigate oxidative stress. The study found a strong positive relationship between SOD and both time and Cd pollution. However, CAT exhibited inhibition throughout the later stages of the experiment, particularly when exposed to relatively higher levels of pollution. The analysis of RNA in earthworms revealed that soil Cd pollution at a concentration of 2.5 mg/kg primarily impacts the cellular structure and function of earthworms. This pollution disrupts the integrity of the cytoskeleton structure, hampers DNA replication, and compromises the precision of cell signaling. Simultaneously, when compared to the control group, several metabolic pathways exhibited abnormalities.